Bees visitors Mouriri acutiflora (Melastomataceae) using the floral oil as a resource? - Oliveira, Fabiana dos Santos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Melastomataceae is a family of abundant and diverse plants. In some genera of the subfamily Memecyloideae, as Mouriri acutiflora, floral oil resource is offered. The aim of this study was to examine relationships between M. acutiflora and visitors regarding the use of floral oil. Aspects of phenology, floral biology, breeding systems and pollinator activity (August/2008 to December/2009) were checked. The flowering of M. acutiflora is annual and intermediate, with fruiting extending from August to February. The species is partially self-incompatible. Poricidal their anthers have elaiophor located in epithelial and connective as pollen and oil resources. Among the visitors, the highest frequencies of visits were from Centris (Centris) caxiensis (Ducke, 1907), Melipona (Mellikerria) fasciculata (Smith, 1854), Xylocopa (Shonnherria) muscaria (Fabricius, 1775) and Xylocopa (Neoxylocopa) frontalis (Olivier, 1789). Evidence of the presence and operation of oil and lipids in anthers necrotic marks on elaiophores, use of oil wetting of pollen grains in M. fasciculata and C. caxiensis show that this species is the source of this resource for visitors.